Supplemental intermittent-day heat training and the lactate threshold. (April 2017) - Gollan, Stuart; Chalmers, Samuel; Alderton, Stephen; Norton, Kevin
Abstract: Heat acclimation over consecutive days has been shown to improve aerobic-based performance. Recently, it has been suggested that heat training can improve performance in a temperate environment. However, due to the multifactorial training demands of athletes, consecutive-day heat training may not be suitable. The current study aimed to investigate the effect of brief (8×30 min) intermittent (every 3–4 days) supplemental heat training on the second lactate threshold point (LT2 ) in temperate and hot conditions. 21 participants undertook eight intermittent-day mixed-intensity treadmill exercise training sessions in hot (30 °C; 50% relative humidity [RH]) or temperate (18 °C; 30% RH) conditions. A pre- and post-incremental exercise test occurred in temperate (18 °C; 30% RH) and hot conditions (30 °C; 50% RH) to determine the change in LT2 . The heat training protocol did not improve LT2 in temperate (Effect Size [ES]±90 confidence interval=0.10±0.16) or hot (ES=0.26±0.26) conditions. The primary finding was that although the intervention group had a change greater than the SWC, no statistically significant improvements were observed following an intermittent eight day supplemental heat training protocol comparable to a control group training only in temperate conditions. This is likely due to the brief length of each heat training session and/or the long duration between each heat exposure. Highlights: Supplementing habitual training with brief heat training did not improve performance. The break between training sessions may need to be ≤3 days to improve performance. Longer duration training sessions (>30 min) may be required to improve performance.